Influence of Diabetes on Morphometric Index of Ovarian Follicles in Streptozocin-Induced Rats - Serpil Ünver Saraydin; Berna Özdenoglu Kutlu; Dursun Saraydin (Medical Laboratory Technology Journal, 2022)
The study aimed to determine the effect of diabetes on follicle development by measuring the diameters of rats' ovarian follicles. The structure and function of many organs change by being affected by diabetes. The ovary is an essential organ of the reproductive system affected by diabetes. The size of the ovarian follicles and corpus luteum can also be affected by diabetes. For this reason, body mass, blood glucose level, and rat ovarian follicles, and corpus luteum diameters were measured in this study. Ten healthy female rats were kept as the control group. In the other rat group, experimental diabetes was induced with streptozotocin (STZ)(60 mg/kg). The rats in both groups were killed after 30 days and their ovaries removed. 5-6 µm sections were made using paraffin embedding techniques and stained with hematoxylin-eosin. On the fifth day of STZ administration to rats, the mass loss of rats was 10%, and the diabetogenic index was 330%. Compared with the control group, diameters of diabetic rats significantly decreased the diameter of the primordial, primary and Graafian follicles, and corpus luteum. The decrease in the diameter of secondary follicles of diabetic rats was not significant. The percentage shrinkage index was the highest in the corpus luteum with 37%. As a result, it can be said that diabetes influences the size of the ovarian follicles and especially the corpus luteum, thereby negatively affecting the ability to improve oocyte quality. Diabetes-related follicle diameter may shrink and cause infertility. It may be essential to measure the diameters of the follicles in vitro fertilization studies in patients with diabetes.